Managing Time and Stress during a Pandemic - Christian K Hansen (Academic Chairpersons Conference Proceedings, 2022)
In this workshop we discuss time and stress management specifically from the perspective of an academic department chair leading an academic department through a pandemic. The focus will be on practical strategies for effective use of time, not only at a personal level, but also at a department wide level, when there are limited opportunities to interact on a daily basis. In this live virtual workshop, participants will have the opportunity to engage in small group discussions via Zoom breakout rooms.
Keywords: Time management; stress management; productivity; virtual meetings; remote staff